2004
DOI: 10.1007/bf02872407
|View full text |Cite
|
Sign up to set email alerts
|

Study of adenosine deaminase activity in pulmonary tuberculosis and other common respiratory diseases

Abstract: Tuberculosis has, in a short span of time, become a major health problem in the third world or developing countries like India. In view of this, a retrospective study was conducted to study Adenosine deaminase activity in serum and pleural fluid in patients affected with Pulmonary Tuberculosis and other common non-tubercular chronic respiratory diseases. The study was carried out on 100 patients suffering from various pulmonary disorders, between January 2002 and August 2002. Thirty-five normal healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In present study, the serum ADA activity was increased in pulmonary tuberculosis patients when compared to healthy controls and the difference was statistically significant (p <0.001). This was in conformance with the work of researchers Rao et al, Amniafshar S et al, Verma M et al, and Lakshmi et al [25][26][27][28] The serum ADA activity >30U/L and pleural fluid ADA activity >40U/L were considered as the diagnostic cut off values in pulmonary tuberculosis with pleural effusion. 29 In present study, the serum ADA activity was significantly increased (p<0.001) in pulmonary tuberculosis patients with pleural effusion when compared to healthy controls, transudative pleural effusion and exudative pleural effusion in conformance with study of Sonone et al 30 In present study, the pleural fluid ADA activity in pulmonary tuberculosis patients with pleural effusion was significantly increased (p<0.001) when compared to transudative and non-tuberculous exudative pleural effusion controls which was in agreement with Sonone et al, Devkota et al, Gupta BK et al, and Lee et al [30][31][32][33] The pleural fluid ADA level rarely exceeds the cut off limit of >40U/L in nontuberculous lymphocytic effusions.…”
Section: Discussionsupporting
confidence: 87%
“…In present study, the serum ADA activity was increased in pulmonary tuberculosis patients when compared to healthy controls and the difference was statistically significant (p <0.001). This was in conformance with the work of researchers Rao et al, Amniafshar S et al, Verma M et al, and Lakshmi et al [25][26][27][28] The serum ADA activity >30U/L and pleural fluid ADA activity >40U/L were considered as the diagnostic cut off values in pulmonary tuberculosis with pleural effusion. 29 In present study, the serum ADA activity was significantly increased (p<0.001) in pulmonary tuberculosis patients with pleural effusion when compared to healthy controls, transudative pleural effusion and exudative pleural effusion in conformance with study of Sonone et al 30 In present study, the pleural fluid ADA activity in pulmonary tuberculosis patients with pleural effusion was significantly increased (p<0.001) when compared to transudative and non-tuberculous exudative pleural effusion controls which was in agreement with Sonone et al, Devkota et al, Gupta BK et al, and Lee et al [30][31][32][33] The pleural fluid ADA level rarely exceeds the cut off limit of >40U/L in nontuberculous lymphocytic effusions.…”
Section: Discussionsupporting
confidence: 87%
“…The mean serum ADA activity in pulmonary TB patients was 35.5 ± 6.93 U/L as 52 compared to 16.20 ± 2.85 U/L in control group, showing highly significant (P<0.001) difference. ADA activity was highest in tuberculosis than compared to controls (21) . Jhamaria JP et al, in 1988 estimated serum ADA level in 20 healthy controls, 102 cases of pulmonary tuberculosis, 20 cases of suppurative lung diseases (lung abscess and bronchiectasis) and 18 cases of lung malignancy.…”
Section: Discussionmentioning
confidence: 68%
“…This enzyme irreversibly converts adenosine to inosine and deoxyadenosine to deoxyinosine, and the speed rate of this reaction gives an account of enzymatic activity, calculated as ADA concentration in the laboratory. 8 A meta-analysis of studies done from 1966 to 1999 displayed that the efficiency of the ADA test in diagnosing tuberculous pleural effusion was acceptable and it was reported that its sensitivity varied from 47.1% to 100% while its specificity ranged from 0% to 100%. 5 This meta-analysis is representative of the diversity of results among the published studies.…”
Section: Introductionmentioning
confidence: 99%